ANALISIS RASIO UNTUK MENILAI KINERJA KEUANGAN PERIODE TAHUN 2017/2018 DI PERUSAHAAN SAMINO KONVEKSI - Tati Indriani; Intan Hapsarie Pratiwi (Jurnal Manajemen, 2020)
Abstract This study aims to determine the level of performance conditions of Samino Konveksi by using financial ratio analysis during the period 2017 to 2018. Financial ratio analysis has four types, namely liquidity ratios using the current ratio, asset management ratios using inventory turnover ratio and total asset turnover ratio, debt management ratio using debt ratio, and probability ratio using return on total assets. The method in the study is descriptive. The type of data used is secondary data, namely financial statements in the form of balance sheets and income statements. The results of the study show (1) Liquidity, the current ratio of the company in 2017 is improving. 2018 worsens. (2) Solvency, the company's Debt ratio in 2017 is improving. 2018 worsens. (3) Activities, the company's inventory turnaround in 2017 deteriorates. 2018 is improving. (4) Profitability, in 2017 and 2018 there is no change (fixed). Keywords: Financial Performance Analysis (Liquidity, Solvability, Profitability Activities)